Two new inorganic-organic hybrid compounds: photocatalytic, luminescent property and treatment activity on polycystic ovary syndrome. Issue 1 (1st January 2021) - Shi, Ping-Ping; Li, Li-Li
Abstract: Two new mixed-ligand-based compounds, namely [Co(1, 3-pde)(4-bpmh)]n (1 ) and [Zn3 (3, 3'-bpdc)3 (4-bpmh)1.5 ]n (2 ) (1, 3-H2 pde = 1, 3-phenylenediacetic acid, 3, 3'-H2 bpdc = biphenyl-3, 3'-dicarboxylic acid, 4-bpmh = N, N-bis-pyridin-4-ylmethylene-hydrazine) have been prepared under hydrothermal conditions. The obtained compounds were determined by singe crystalX-ray diffraction analyses, elemental analyses, powder X-ray diffraction analyses and thermogravimetric analyses. Moreover, the photocatalytic activity of 1 and luminescent property of 2 have also been investigated. This presented research estimate their treatment activity of the polycystic ovary syndrome, also the mechanism was measured as well. Firstly, a relative expression of the estrogen receptor on the ovarian epithelial cells was determined with real time RT-PCR. In addition, the amount of progesterone of the plasma was measured with ELISA detection kit after indicated treatment.